MANAJEMEN MULTIMEDIA BERBASIS SMART TV TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA - Rahman, Anwar (Kelola: Journal of Islamic Education Management, 2023)
This study aims to find out how Smart TV-based multimedia management improves the learning motivation of Grade VIII students in English at MTs Negeri Luwu. This research uses the Mix Methode research method which is presented qualitatively and quantitatively. The data sources used are primary and secondary data obtained from interviews, observations, questionnaires and documentation. The results of this study indicate that students have high learning motivation in English subjects at MTs Negeri Luwu when the teacher manages or manages and uses Smart TV-based multimedia in the classroom. Smart TV-based multimedia management is carried out in several stages, namely: 1) Planning aspects which include adjusting materials, preparing supporting facilities/infrastructure and installing Smart TV devices and internet networks. 2) The implementation aspect that before the teacher explains the material, the first thing to do is to check the availability of the tools used, such as laptops, smartphones, network connections, electricity, and appropriate learning methods. 3) The evaluation aspect that all stages have been carried out in accordance with the procedure so that this multimedia is very helpful for teachers presenting class material and motivating students to learn, especially in English subjects.Â The inhibiting factor in Smart TV-based multimedia management is the internet network which is usually unstable, and the electricity sometimes goes out while the supporting factors in multimedia management are the availability of supporting facilities and infrastructure in the use of Smart TV-based multimedia such as Wifi Internet, active speakers, good classroom lighting and besides that the teachers have been able to operate this Smart TV-based multimedia trough training they have attended before using it in classÂ